Música e estudos para a paz: uma relação harmônica para construção de paz em áreas de conflito - Braga, Lívia (2020)
In the human evolutionary process, basic elements such as language and music, conflict and violence, can be found. Studies for Peace in this scenario, when analyzing and discussing the structural problems of a conflict, provide the development of individuals, the transformation of the environment, leading to Peacebuilding. Music, as a unifying instrument, can also be the adopted practice in this process. In this way, this work is composed of an analysis between the two theoretical and practical fields Music and Peace Studies, and their applicability to Peacebuilding in conflict areas. Guiding the methodology in a qualitative approach, a bibliographic survey was carried out, based on works arranged in physical and virtual databases. Given the interdisciplinary nature of the theme, the theoretical framework dialogues with areas such as musicology, ethnomusicology, international relations, neuroscience, political science, psychology, philosophy, sociology, among others. In view of this outlined structure, the research is divided into four chapters: in the first, the sound phenomenon and the other fields related to it and human evolution such as language and music, conflict and violence are described; and, the meaning attributed to art and music for the Greeks. In the second chapter, focusing on music, a brief narrative is made about its importance, from ancient Greece to modernity; some concepts that are connected to the theme of Peacebuilding are addressed; its influence in the human cognitive and behavioral area, and finally, a question is asked about the active political role of musicology as a science. The concepts of Peace; the initiation of Research for peace until consolidation in Studies for Peace; in addition to an exhibition on Peacebuilding and the existing mechanisms to achieve this purpose, these are the points presented in the third chapter. Based on these, a reflection on the function of music arises in the last chapter, an element that inflames or pacifies the life of the human being, of a society. Next, music is pointed out as a relevant instrument in conflict transformation and some examples are used to support this premise, the story of Vedran Smailović, the role of the West-Eastern Divan Orchestra, and the Israeli-Palestinian Jerusalem Youth Chorus choir.